Analysis of the Relationship Between Tooth Brushing Frequency and the Prevalence of Caries in Children Aged 3-5 Years at Aisyiyah Kindergarten, Kemantren Tulangan, Sidoarjo: Analisis Hubungan Antara Frekuensi Menyikat Gigi dan Prevalensi Karies Anak Usia 3-5 Tahun di TK Aisyiyah Kemantren Tulangan Sidoarjo - Yuliartanti, Windy; Purwanti, Yanik; Setyawardhana, Eka; Sari, Wanda Karisma Dian (Universitas Muhammadiyah Sidoarjo, 2025)
Dental caries is one of the most common health issues among young children, especially in developing countries like Indonesia. This study aims to analyze the relationship between toothbrushing frequency and the prevalence of dental caries in children aged 3–5 years at TK Aisyiyah Kemantren Tulangan, Sidoarjo. A quantitative, cross-sectional design was used with a total of 38 child respondents. Data were collected through questionnaires given to parents, addressing children's toothbrushing habits and caries incidence. Results showed that 5-year-old children had a higher prevalence of caries (76.47%) compared to those aged 3 and 4. A total of 14 children (36.85%) experienced caries, while 24 children (63.15%) did not. Children who brushed their teeth twice a day had a lower caries prevalence (30%) than those who brushed once a day (70%). The study also highlighted the role of parental supervision in toothbrushing habits and its association with reduced caries incidence. Additionally, frequent consumption of sugary foods was identified as a contributing factor. In conclusion, a higher frequency of toothbrushing is associated with a lower prevalence of dental caries. Oral health education involving parents and a holistic approach to oral hygiene are crucial in preventing dental caries in children. Ongoing education programs at both school and home environments are necessary to promote proper oral hygiene behaviors from an early age. Highlights: Caries prevalence highest in 5-year-olds (76.47%). Twice-daily brushing linked to lower caries (30% vs 70%). Parental supervision and diet strongly influence caries risk. Keywords: toothbrushing frequency, dental caries, early childhood, oral hygiene, parental involvement